Pelatihan Pembuatan Grafik Untuk Penyajian Data Laporan - Teguh, Rizani; Iba Ricoida, Desy; Rusbandi, Rusbandi (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2023)
Srijaya Negara Palembang High School partners want to increase students' level of understanding regarding the use of Microsoft Excel, especially in making graphs. The MDP University Service Team carries out this activity in the form of training, which aims to increase students' understanding of Microsoft Excel which is carried out using presentation, practice and question and answer methods. The training activity was attended by 36 student participants and 2 accompanying teachers and was carried out well and smoothly according to the planned schedule. The results of the training activities were based on indicators from questionnaire questions to participants, overall in the